Etude de l’effet antagoniste de quelques champignons marins sur Staphylococcus epidermidis - BAALI, Halima; NOURINE, Hayat (My University, 2025)
Staphylococcus epidermidisis a bacterium naturally present on the skin, playing a protective role against pathogenic microbes. It contributes to the balance of the microbiota and the regulation of the immune system. This species can become pathogenic in immunocompromised individuals or those with medical devices. It is recognized as an opportunistic agent due to its ability to form biofilms and its resistance to antibiotics, which increases its virulence. This work is part of the use of metabolites extracted from marine fungi to combat the growth and formation of biofilms in Staphylococcus epidermidis This study first involved isolating and identifying Staphylococcus epidermidis from the nasal cavities, assessing their sensitivity to antibiotics, and their ability to form biofilms, using crystal violet tube and Congo red methods. A second approach focused on the in vitro evaluation of antistaphylococcal activity (inhibition of growth and biofilm) by metabolites extracted from fungi isolated from sea sand at Salamandre beach in Mostaganem. The results obtained reveal the isolation of four Staphylococcus epidermidis isolates. These isolates showed resistance to oxacillin and azithromycin, and biofilm formation. Microbiological analysis of the marine sand samples led to the isolation of 25 fungal isolates. These isolates were tested for their antagonistic activity against Staphylococcus epidermidis using the cross-inhibition technique, with vertical streaks on Mueller-Hinton (MH) medium. Only six fungal isolates (S2, S7, S10, S11, S12, and S32) showed positive antagonistic activity against S. epidermidis. Among these fungal isolates, all identified as belonging to the genus Aspergillus, the most active isolate was morphologically characterized as Aspergillus niger. The secondary metabolites produced by this isolate were extracted using ethyl acetate, and their antistaphylococcal activity was evaluated in vitro using the disk diffusion method. The results revealed an inhibitory effect against Staphylococcus epidermidis, with inhibition zones ranging from 8.9 to 19.35 mm. Finally, the antibiofilm activity of the Aspergillus niger extract was evaluated using the crystal violet tube staining method, revealing an inhibitory effect with inhibition percentages ranging from 38% to 59%.
Keywords: Marine fungi - Staphylococcus epidermidis - Antibiogram - Biofilm formation - Secondary metabolites - Antagonism - Antimicrobial activity